2021
DOI: 10.3389/fmolb.2021.698337
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Spectroscopy in Clinical Metabolomics and Personalized Medicine: Current Challenges and Perspectives

Abstract: Personalized medicine is probably the most promising area being developed in modern medicine. This approach attempts to optimize the therapies and the patient care based on the individual patient characteristics. Its success highly depends on the way the characterization of the disease and its evolution, the patient’s classification, its follow-up and the treatment could be optimized. Thus, personalized medicine must combine innovative tools to measure, integrate and model data. Towards this goal, clinical met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 233 publications
(317 reference statements)
0
51
0
3
Order By: Relevance
“…Gornet et al [96] found that MRS scores, using structural integrity markers (carbohydrate/collagen and PG) expected to decrease with disc degeneration and acidic pain markers (alanine, lactate, and propionate) expected to increase with hypoxia and inflammation, could be obtained by quantifying spectral features from optimized clinical MRS data identified painful discs in patients with chronic LBP with a sensitivity of 82% and a specificity of 88% when compared to provocative discography. As MRS targets the measurement of trace metabolites with signal intensity much lower than that of MRI, the spatiotemporal resolution is low at current clinical MRI field strengths [97]. The widespread use of high-field MRI in the future may expand the clinical application of MRS, which can provide biochemical information.…”
Section: Mr Spectroscopy (Mrs)mentioning
confidence: 99%
“…Gornet et al [96] found that MRS scores, using structural integrity markers (carbohydrate/collagen and PG) expected to decrease with disc degeneration and acidic pain markers (alanine, lactate, and propionate) expected to increase with hypoxia and inflammation, could be obtained by quantifying spectral features from optimized clinical MRS data identified painful discs in patients with chronic LBP with a sensitivity of 82% and a specificity of 88% when compared to provocative discography. As MRS targets the measurement of trace metabolites with signal intensity much lower than that of MRI, the spatiotemporal resolution is low at current clinical MRI field strengths [97]. The widespread use of high-field MRI in the future may expand the clinical application of MRS, which can provide biochemical information.…”
Section: Mr Spectroscopy (Mrs)mentioning
confidence: 99%
“…On the other hand, 1D NMR spectra can be rapidly collected within minutes. While use of NMR is still relatively limited in clinical diagnostics, there are increasing numbers of hospitals with NMR machines for metabolomics analysis of patient samples, for example for cardiovascular disease, diabetes, and cancer (31). These newly identified metabolites may also be translated to other more targeted methods that are faster and less costly than NMR, such as biosensors or immunoassays (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…NMR-based metabolomics offers many advantages in biomarker development. NMR is a high-throughput method requiring minimal sample preparation, allowing quantitative analysis with excellent reproducibility and unlike commonly used techniques, such as mass spectrometry, simultaneously measures all of the more abundant compounds within a biological sample [ 34 , 35 ]. Urine has been proposed as the preferred medium for biomarker development in neurological diseases including SMA, since it is readily available and easily obtained in a non-invasive manner and more importantly, unlike blood and cerebrospinal fluid, lacks homeostatic mechanisms that might attenuate systemic fluctuations, thus more adequately reflecting disease-specific changes [ 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%